Maternal reporting of behaviour following very severe blunt head injury. Issue 5 (May 1991) - Kinsella, G; Packer, S; Olver, J
Abstract : Mothers of 40 very severely head injured male subjects rated their son's behaviour on the Current Behaviour Scale and their ratings were compared with mothers' ratings of 40 control male subjects. The scale was able to discriminate the two groups, by utilising two factors–loss of emotional control and loss of motivation. The mothers' level of emotional distress was closely related to their reporting of loss of emotional control in their sons, but reporting of loss of motivation, or lowered arousal, was strongly predicted by the functional disability of the son. The utility of refining the measurement of post-trauma behaviour is discussed.